Mergers and Accounting Performance: Some Evidence from Greece during the Economic Crisis - Michail Pazarskis; George Drogalas; Andreas Koutoupis (Journal of Accounting and Management Information Systems (JAMIS), 2018)
The study examines the impact of mergers on the accounting performance of merger-involved firms in Greece. The study analyses four basic profitability ratios from financial statements of a sample of sixty Greek listed firms at the Athens Exchange that executed as acquirers' one merger in the period a ten-year-period (2005-2014). In order to measure firms' accounting performance, comparisons of pre- and post-merger firm profitability are examined for one year before and after the merger events (with data analysis from 2004 to 2015). The results revealed that mergers have had a negative impact on profitability and, in general, on accounting performance of the merger-involved firms. Furthermore, the study investigates the impact of the economic crisis on the success of mergers in Greece. There is evidence there is also a negative effect on accounting performance after mergers during the period of the economic crisis in Greece.
Keywords: G34; M40; 650; mergers; accounting performance; financial ratios; economic crisis